(untitled) (Research, Society and Development, 2021)
Chronic obstructive pulmonary disease (COPD) is the champion in causes of mortality and morbidity in the world, characterized by a progressive disorder that leads to respiratory failure due to an obstruction of the expiratory airflow, accompanied by hypersecretion of mucus in different degrees and progressive loss lung function. The aim of this article is to demonstrate the importance of pulmonary rehabilitation in patients with COPD. The study is a literature review of a quantitative and descriptive character, researched in databases such as Public Medlineor Publisher Medline (PubMed), Cochrane Library, Scientific Eletronic Library Online (SciELO) and Brazilian Society of Pulmonology and Tisiology, with the descriptors, “ Obstructive Disease "’," Hypersecretion "," Physiotherapy ". Physiological deficits in COPD include restricted exercise tolerance, limited airflow, pulmonary hyperinflation, respiratory muscle weakness, ventilatory limitation and consequent impairments in quality of life. In this context, pulmonary rehabilitation promotes cardiopulmonary reconditioning, aids in bronchial clearance and equalization of respiratory flows, promotes gains in chest mobility and strengthening of respiratory muscles, increased functional capacity, greater tolerance to exercise, improving the feeling of dyspnea and fatigue It is noticed that pulmonary rehabilitation is an indispensable and supporting tool within the process of clinical improvement of patients with COPD, there are positive gains with regard to quality of life, cardiorespiratory conditioning and a decrease in episodes of acute symptoms and eventual hospitalizations.